2010
DOI: 10.1111/j.1600-079x.2010.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against isoproterenol‐induced myocardial injury in the rat: antioxidative mechanisms

Abstract: The present study was undertaken to explore the protective effect of melatonin against isoproterenol bitartrate (ISO)-induced myocardial injury in rat. Treatment of rats with ISO increased the level of lipid peroxidation products and decreased the reduced glutathione levels in cardiac tissue indicating that this synthetic catecholamine induces oxidative damage following oxidative stress. Pretreatment of ISO-injected rats with melatonin at a dose of 10 mg/kg body weight, i.p. prevented these changes. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 56 publications
9
84
0
1
Order By: Relevance
“…Contrary to several previous studies, our data suggest that ISO did not increase oxidative stress. Karthikeyan, et al, (34) Patel, et al, (35) and Mukherjee, et al (36) reported that ISO causes an increase in oxidative stress markers. However, there were several critical differences between these studies and the current study: (1) animals in the previous studies received repeated doses of ISO, as compared to the single dose administered in the current study, (2) measures of lipid peroxidation and oxidative stress were measured two or more days after the initial dose of ISO, as compared to 24 hours after the initial dose in the current study, (3) all 3 of these studies analysed homogenised myocardium, not circulating plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to several previous studies, our data suggest that ISO did not increase oxidative stress. Karthikeyan, et al, (34) Patel, et al, (35) and Mukherjee, et al (36) reported that ISO causes an increase in oxidative stress markers. However, there were several critical differences between these studies and the current study: (1) animals in the previous studies received repeated doses of ISO, as compared to the single dose administered in the current study, (2) measures of lipid peroxidation and oxidative stress were measured two or more days after the initial dose of ISO, as compared to 24 hours after the initial dose in the current study, (3) all 3 of these studies analysed homogenised myocardium, not circulating plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The most reactive and, therefore, destructive of the ROS is the hydroxyl radical ( OH). Melatonin has repeatedly been shown, using a wide variety of techniques, to rapidly scavenge this reactant when and where it is intracellularly generated; this deprives the OH of the opportunity to destroy critical neighboring molecules [17][18][19][20][21][22]. Melatonin, however, does not restrict itself to scavenging only the OH; rather, it also interacts with and neutralizes with varying degrees of efficiency, singlet oxygen, the superoxide anion radical, hydrogen peroxide and the peroxynitrite anion [23][24][25][26][27].…”
Section: Melatonin: Neutralizing Free Radicalsmentioning
confidence: 97%
“…Thus in addition to DNA, lipids and proteins are also highly vulnerable and are oxidized if free radicals are uncontested; these lesions lead to molecular damage and reduced cellular function. As with DNA, melatonin also protects lipids and proteins from damage by radical products produced as a consequence of ionizing radiation or other processes [18,21,[65][66][67][68][69]. Finally, whereas melatonin is a highly effective protector against free radical damage, the derivatives of melatonin, which as noted above, function as scavengers and likewise efficiently defer molecular damage [28,30,31,70,71].…”
Section: Melatonin: Protecting Macromoleculesmentioning
confidence: 98%
“…Despite these results being contradictory, in addition to melatonin's prime effects on reproductive mechanisms, all of these studies indicate the existence of an uncharacterized relation between melatonin level and uterine contractility. While the beneficial effects of melatonin in different tissues have been studied by researchers, to our best knowledge, there is no any information regarding the effects of melatonin in different concentrations on contraction patterns of the nonpregnant rat uterus (12)(13)(14)(15). On the basis of this background, using an in vivo experimental model, we aimed to explore the physiological and pharmacological concentrations of melatonin on spontaneous and oxytocin-induced contraction patterns of a non-pregnant rat uterus.…”
Section: Introductionmentioning
confidence: 99%